2005
DOI: 10.1191/0960327105ht568oa
|View full text |Cite
|
Sign up to set email alerts
|

Increase in thyroid follicular cell tumors in nelfinavir-treated rats observed in a 2-year carcinogenicity study is consistent with a rat-specific mechanism of thyroid neoplasia

Abstract: The carcinogenic potential of nelfinavir mesylate (nelfinavir) was evaluated in a 2-year oral (gavage) study on Sprague-Dawley rats at dose levels of 0 (control), 0 (vehicle control), 100, 300 and 1000 mg/kg per day. At the end of the treatment, increased incidences of thyroid follicular cell hyperplasia and neoplasms were observed at 300 (males) and 1000 mg/kg per day (both sexes). There were no other treatment-related effects and no tumors at other sites. Results from previous studies indicated a nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…TOXICOLOGIC PATHOLOGY hormone (T4) and elevated TSH via negative feedback on the hypothalamic-pituitary-thyroid axis (Attia and Aref 1991;Ennulat et al 2010;McClain 1989;McClain et al 1989). This hypothesis is supported by results from other hepatic enzyme inducers reported in the literature (Burns-Naas et al 2005;Dixit et al 2007) and from our own findings in the pituitary gland (which were unique to the literature), thyroid gland, and liver. This adaptive physiologic response of the thyroid gland to hepatic enzyme induction and stimulation of the hypothalamic-pituitary-thyroid axis observed in rats treated with RO2910 is a well understood and familiar response in rats, especially in males, treated with high doses of xenobiotics.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…TOXICOLOGIC PATHOLOGY hormone (T4) and elevated TSH via negative feedback on the hypothalamic-pituitary-thyroid axis (Attia and Aref 1991;Ennulat et al 2010;McClain 1989;McClain et al 1989). This hypothesis is supported by results from other hepatic enzyme inducers reported in the literature (Burns-Naas et al 2005;Dixit et al 2007) and from our own findings in the pituitary gland (which were unique to the literature), thyroid gland, and liver. This adaptive physiologic response of the thyroid gland to hepatic enzyme induction and stimulation of the hypothalamic-pituitary-thyroid axis observed in rats treated with RO2910 is a well understood and familiar response in rats, especially in males, treated with high doses of xenobiotics.…”
supporting
confidence: 87%
“…In addition, the increased mitotic activity in the thyroid gland after fourteen days of treatment with RO2910 supports a progression from hypertrophy to hyperplasia. Similarly, other molecules in the same pharmacologic class as RO2910, including darunavir, neviripine, and efavirenz, as well as a number of other inducers of hepatic enzymes, lead to thyroid hormone disruption and/or thyroid tumorigenesis (Burns-Naas et al 2005;Dixit et al 2007). The reason for the unexpected unchanged serum T3 levels in this study may be related to differences among rat strains in thyroid hormone (T4 and T3) response to elevated TRH and TSH, metabolism and inter-individual variability, as demonstrated in Sprague-Dawley and Fischer rats, or to the sampling time FIGURE 8.-Quantitative image analysis of hematoxylin and eosinstained sections of thyroid gland from vehicle control and treated rats with enumeration of follicular cell cytoplasm (A) and colloid content (B) expressed each as the percentage of area within the area of the follicular region.…”
Section: Discussionmentioning
confidence: 99%
“…These pre-formed AChR clusters as NMJs on muscle fibers can enhance direct contacts with host nerve system (innervation) in vivo 29 . It has been also showed that glial cells can support the NMJ formation and tissue maturation, as well as efficient action potential [46][47][48] . Conversely, a study states that co-culture with non-myogenic cells can reduce the levels of myogenic differentiation due to the interruption of muscle cell fusion by other cell types.…”
Section: Discussionmentioning
confidence: 99%
“…The hormone turnover of the rodent thyroid is significantly higher than that of the human thyroid. Evaluating the risks of thyroid tumors in humans based on the exposure to any of these chemicals that have produced thyroid follicular cell tumors in laboratory rodents is difficult (Hard, 1998;Burns-Naas et al, 2005).…”
Section: Discussionmentioning
confidence: 99%